2021
DOI: 10.1002/bin.1815
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of empirical intraverbal research: 2015–2020

Abstract: The impact of Verbal Behavior (Skinner, 1957) on behavior analytic research, although not immediate, has steadily increased. Empirical investigations of verbal operants initially focused on mands and tacts, yet other operants such as intraverbals, echoics, and autoclitics have started to receive more attention. Aguirre et al. (2016) reviewed intraverbal research between 2005 and 2015. The results showed an increase in intraverbal research, with studies mostly focused on direct intraverbal training and emergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 102 publications
(113 reference statements)
0
16
0
1
Order By: Relevance
“…The results from this line of research may inform clinical practice. In a recent review of intraverbal research, Jennings et al (2021) found that intraverbals were most commonly established using direct training with echoic prompts. The current line of research suggests instead of directly teaching intraverbals, a more advantageous and efficient approach would be to establish repertoires that could lead to emergent intraverbals.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this line of research may inform clinical practice. In a recent review of intraverbal research, Jennings et al (2021) found that intraverbals were most commonly established using direct training with echoic prompts. The current line of research suggests instead of directly teaching intraverbals, a more advantageous and efficient approach would be to establish repertoires that could lead to emergent intraverbals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reviews focused on more broadly on the intraverbal or emergent verbal behavior have identified varying numbers of studies in this area, ranging from 16 (DeSouza et al, 2017) to 30 (Raaymakers et al, 2019) to 31 (Aguirre et al, 2016) to 52 (Pérez-González, 2020). The inconsistency in the number of studies identified notwithstanding, many of these authors have directly called for more in-depth reviews on emergent intraverbal behavior (Aguirre et al, 2016;DeSouza et al, 2017;Jennings et al, 2021). Some limitations of these review papers also indicate a need for further work in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting a focused review on behaviors that were themselves not directly trained but established by training some other type of response (i.e., emergent) requires a unique approach to coding. For example, Jennings et al (2021) conducted the most recent review of the intraverbal literature as a whole (extending Aguirre et al, 2016) and included variables related to direct training such as prompts, prompt-fading, error correction, and putative reinforcers. These variables are of clear value when investigating the outcomes of transfer-of-stimulus control procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The objective evaluation of acts of communication is often complex, as the words used can serve different communicative functions (Jennings et al, 2021). A verbal instance's effect on the listener determines the verbal function; he acts as a mediator in the person's interest; the latter uses the person listening to mediate the environment (Cooper et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many interventions have proven effective in enhancing conversational skills (Jennings et al, 2021). Some studies have focused on evaluating the effectiveness of using text prompts (Swerdan & Rosales, 2017).…”
Section: Introductionmentioning
confidence: 99%